Early 18th Century Hand Grenades on the North American Atlantic Coast: An Experimental Archaeology Study - Lacey, Stephen (East Carolina University, 2019)
In the first half of the eighteenth century, standardization of weapons appears in cannon, shot, and small arms. No comparative study has been conducted to determine if grenades follow this pattern. In this study, three collections of cast iron grenades dating from 1700-1750 were compared to determine if any statistical significance exists. If so, this will form the basis to create a taxonomy to assist in dating sites. Furthermore, grenade blasts from this era are reported in the historical record but recorders barely understood ballistics. An experimental phase has been designed into the project to fully record a blast via controlled detonation. The concussive force and decibel levels were recorded to help assess potential damage. Upon completion, medical evaluations can be made to determine the full lethality of cast iron grenades. This allows an evaluation of historical records for unexplained deaths, altered behaviors post battle, and critical evaluation of historical documents on grenade lethality.
Keywords: Naval Combat; Maritime History; Grenades--North America--History--18th century; Experimental archaeology--North America--History--18th century